Towards a Legacy of the Scottish Tradition: The Democratic Intellect in America. Issue 2 (June 2019) - Clark, Duane
Abstract : This paper addresses one of the themes of the 2018 CSSP Conference: understanding the legacy of the Scottish tradition. In doing so I suggest that we find some Scottish heirlooms in early American education. To make this case I will start with a text that has been largely refuted and establish a starting point for a legacy of the Scottish tradition with what I believe to be the weakest case: the almost unknown Glaswegian philosopher George Jardine (1742–1827).